Atmospheric Composition Observations - Armin Sorooshian (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
The composition of the atmosphere is a critical factor in understanding the nature and magnitude of processes associated with the planet's energy balance, clouds and precipitation, biogeochemical cycling of nutrients, and public health and welfare. A detailed understanding of trace gases, aerosol particles, and hydrometeors is challenging due to the combination of their physicochemical complexity, variable lifetimes, and spatial inhomogeneity. Recent advances in instrumentation have resulted in improved measurements and an increased understanding of atmospheric composition. Laboratory and field in-situ measurement studies have benefited from such improvements, including improved spatial and temporal resolution, the ability to sample in challenging conditions (e.g., on airborne platforms, in clouds, at widely ranging pressure and temperature conditions), and the ability to measure a wider range of chemical species, and, in the case of aerosol particles, to detect smaller sizes. Remote sensing capabilities have increased in recent years, thus offering new views of atmospheric composition across broad spatiotemporal ranges. Manuscripts related to all aspects of atmospheric observations are included in this Special Issue, including advances in observational techniques and scientific insights into atmospheric composition.